Institutional policies on plagiarism: The case of eight Chinese universities of foreign languages/international studies. (June 2017) - Hu, Guangwei; Sun, Xiaoya
Abstract: Plagiarism is a major problem for universities worldwide and has been a constant cause of concern in higher education. Previous research has focused on Chinese students' attitudes toward, knowledge of, and engagement in plagiarism in Chinese and overseas educational contexts, and there is also a growing body of research on Chinese teachers' understandings of and stance on plagiaristic practices. However, little research attention has been given to institutional policies on plagiarism in the Chinese context, though similar research has been conducted in other settings. This paper reports on a study that examines the plagiarism policies made publicly available by eight major universities of foreign studies in mainland China. Both the structure and content of these universities' policy documents are analyzed to identify institutional understandings of, attitudes toward, and sanctions on plagiarism. The analysis reveals that despite inter-institutional variations, the policy documents are dominated by moralistic and regulatory discourses and are characterized by the conspicuous lack of an educative approach to plagiarism. We argue that such an institutional approach to plagiarism is unlikely to be effective because it largely fails to support students' acquisition of academic literacy and legitimate intertextual practices.